2022
DOI: 10.4014/jmb.2208.08017
|View full text |Cite
|
Sign up to set email alerts
|

The Ingestion of Dietary Prebiotic Alternatives during Lactation Promotes Intestinal Health by Modulation of Gut Microbiota

Abstract: Palm kernel expeller (PKE), a by-product of palm oil extraction, contains higher amounts of fiber than corn and soybean meal, but offers low energy density, protein value, and amino acid (AA) composition, limiting its use for swine. Recently however, it was reported that dietary fiber has a positive effect on the gut microbiota of the host, and therefore it is necessary to study the effect of PKE feeding on the intestinal microbiota of swine. In this study, we investigated the effects of supplementation with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Another hypothesis is that the caring environment plays a crucial role in the function and composition of the gut microbiota during both the suckling and weaning periods [ 42 , 45 ]. Our previous studies confirmed that the nutritional changes in sow diets affected the sow and piglet health and gut microbiota [ 46 , 47 ]. The present study observed similar gut microbial profiles, with increases in the genus Lactobacillus and Ruminococcus and decreases in the genus Bacteroides , Escherichia/Shigella , and Clostridium , in both the sows and piglets when the sows were fed a SDP additive diet during lactation.…”
Section: Discussionsupporting
confidence: 86%
“…Another hypothesis is that the caring environment plays a crucial role in the function and composition of the gut microbiota during both the suckling and weaning periods [ 42 , 45 ]. Our previous studies confirmed that the nutritional changes in sow diets affected the sow and piglet health and gut microbiota [ 46 , 47 ]. The present study observed similar gut microbial profiles, with increases in the genus Lactobacillus and Ruminococcus and decreases in the genus Bacteroides , Escherichia/Shigella , and Clostridium , in both the sows and piglets when the sows were fed a SDP additive diet during lactation.…”
Section: Discussionsupporting
confidence: 86%
“…Growing interest in gut microbiota has prompted research into their interactions with hosts in various contexts, including environmental changes and diseases [ 12 - 16 ]. Recent studies have particularly focused on the role of gut microbiota in organ transplantation and their influence on immune regulation in transplant recipients [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial taxa mediating SCFA production, such as the family Lachnospiraceae [ 31 ], genera Streptococcus [ 29 ], and Ruminococcus [ 32 ] were more abundant in SPF pigs (20.0%, 60.2%, and 8.3%, respectively) than in non-SPF pigs (4.9%, 33.3%, and 3.1%, respectively). Moreover, the genera Blautia [ 31 , 33 ], Bacteroides [ 33 , 34 ], and Roseburia [ 16 , 35 ] were exclusively found in SPF pigs (4.1%, 3.4%, and 1.9%, respectively). However, the association between a low proportion of Prevotella in the gut microbiota and the pathogen-free environment requires further confirmation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation